Glicemia mal controlada como factor de riesgo de neuropatía periférica en diabéticos tipo 2 - Mantilla Cruzado, Víctor Arturo (2017)
Poorly controlled glycemia has been described as one of the main risk factors for complications in diabetic patients. Objective: To determine if poorly controlled glycemia is a risk factor for peripheral neuropathy in type 2 diabetics. Methodology: A case-control study was conducted, the sample was collected between January and June 2017 in a nursing topic before patients admitted to consultation, the group of cases was made up of 64 patients and the group of controls also by 64 patients. Results: 41 male patients (32.03%) and 87 female patients (67.97%) were studied, the average age was 53.22 years, the frequency of neuropathy was 49.33%. The frequency of poorly controlled glycemia in patients with and without peripheral neuropathy was 59.38% and 34.38% respectively. Likewise, an OR of 2.79, a Chi-square of 7.97 and a confidence interval between 1.37 and 5.69 were found. Conclusion: Poorly controlled glycemia is a risk factor for peripheral neuropathy in type 2 diabetics